ECO-FRIENDLY STRATEGIES FOR CONTROLLING HOUSE MICE AND OVERCOMING TRAP-SHYNESS - Samira Hajialiloo bonab; Gholamhossein Moravvej; Roohollah Siahsarvie (Journal of Animal and Plant Sciences, 2026)
House mice (Mus musculus) are invasive rodents that pose serious challenges in urban and rural environments by contaminating food, transmitting diseases, and disrupting ecosystems. One of the major obstacles to effective control is trap-shyness, a learned behavioral avoidance following initial trap exposure. This study evaluated eco-friendly strategies to control house mouse populations while mitigating trap-shyness through improved trap design, bait selection, optimized placement, and behavioral camouflage. A novel approach involved camouflaging traps with mud to reduce visual and tactile detection by mice. Following the onset of trap-shyness, capture rates increased markedly after trap camouflaging, rising from 5–11 to 67–98 mice per store. Rodent activity, assessed via food consumption, declined substantially by over 90% in store 1 (from 735 to 40 g( and store 2 )from 398 to 34 g), and by 86.5% in store 3 (from 549 to 74 g). Statistical analysis confirmed that trap camouflaging significantly reduced trap-shyness (P < 0.05). By integrating behavioral ecology with sustainable pest management techniques, this study demonstrates an effective, non-chemical approach for house mouse control. The findings provide practical and environmentally responsible solutions for pest management professionals and researchers.
Keywords: Mus musculus; Camouflage techniques; Wildlife management; Rodent control; Trap-shyness